Internal-Flow-Mediated, Tunable One-dimensional Cassie-to-Wenzel Wetting Transition on Superhydrophobic Microcavity Surfaces during Evaporation. Issue 4 (2nd October 2019) - Pendyala, Prashant; Kim, Hong Nam; Grewal, Harpreet S.; Chae, Uikyu; Yang, Sungwook; Cho, Il-Joo; Song, Simon; Yoon, Eui-Sung
ABSTRACT: Superhydrophobic textured surfaces are known to maintain a nonwetted state unless external stimuli are applied since they can withstand high wetting pressure. Herein, we report a new category of tunable, one-dimensional (1D) Cassie-to-Wenzel wetting transitions during evaporation, even on superhydrophobic surfaces. The transition initiates at the periphery of the evaporating drop, and the wetting transition propagates toward the center of the drop. The transitions are observed for surfaces with wetting pressures as high as 7, 568 Pa, which is much higher than the Laplace pressure, i.e., 200 Pa. In situ high-contrast fluorescence microscopy images of the evaporating drop show that the transition is induced by preferential depinning of the air-water interface and subsequent formation of air bubbles in the cavities near the three-phase contact line. The evaporation-induced internal flow enhances the pressure within the water droplet and subsequently causes a Cassie-to-Wenzel wetting transition.